Numerical procedure for long-term deflection prediction of RC elements subjected to different load histories - Docevska, M., Markovski, G., Arangjelovski, T., Nakov, D., Mark, P. (MASE - Macedonian Association of Structural Engineers Faculty of Civil Engineering, ul. Partizanski odredi br. 24 P.Box. 560, 1000 Skopje, Republic of Macedonia, 2017)
The influence of expected but idealized load histories typical for structural service conditions during life-time was studied with a special emphasis on long-term serviceability of RC structures. For that purpose, a numerical step-by-step cross-sectional procedure based on the Age-Adjusted Effective Modulus Method (AAEMM) has been developed and successfully verified through existing experimental results applying it on simply supported RC beams and one-way slabs. First results confirmed that individual load histories and precisely tracking the stiffness reduction with time, are significant to realistically reflect the long-term behavior of RC elements.
Keywords: step-by-step, load history, long-term deflections, moment-curvature relations